(untitled) (Estudos Japoneses, 2020)
This article analyses the current status of elderly rights in Japan from the perspective of international Human Rights. It discusses the status of older people as a group that needs specific protections and evaluates the existence of their rights in the International Human Rights System. In addition, it reviews the development of the elderly rights in the Japanese State and analyses their protection from the perspective of the main international Human Rights instruments.